A Potential High-Risk Clone of Pseudomonas aeruginosa ST463 - Hu, Yanyan; Peng, Wenjing; Wu, Yifan; Li, Hui; Wang, Qi; Yi, Huahua; Zhang, Rong; Shao, Bing; Zhu, Kui (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa is one of the most common opportunistic pathogens, which causes severe nosocomial infections because of its well-known multidrug-resistance and hypervirulence. It is critical to curate routinely the epidemic P. aeruginosa clones encountered in the clinic. The aim of the present study was to investigate the connection between virulence factors and antimicrobial resistance profiles in epidemic clones. Herein, we found that ST463 (O4), ST1212 (O11), and ST244 (O5) were prevalent in 30 isolates derived from non-cystic fibrosis patients, based on multilocus sequence type (MLST) and serotype analysis. All isolates were multidrug-resistant (MDR) and each was resistance to at least three classes of antibiotics in antimicrobial susceptibility tests, which was consistent with the presence of the abundant resistance genes, such as blaOXA-50, blaPAO, aph(3'), catB7, fosA, crpP, and blaKPC-2. Notably, all blaKPC-2 genes were located between ISKpn6-like and ISKpn8-like mobile genetic elements. In addition, classical exotoxins encoded by exoU, exoS and pldA were present in 43.44% (13/40), 83.33% (25/30), and 70% (21/30) of the isolates, respectively. The expression of phz operons encoding the typical toxin, pyocyanin, was observed in 60% of isolates (18/30) and was quantified using triple quadrupole liquid chromatograph mass (LC/MS) assays. Interestingly, compared with other MLST types, all ST463 isolates harbored exoU, exoS and pldA, and produced pyocyanin ranging from 0.2 μg/mL to 3.2 μg/mL. Finally, we evaluated the potential toxicity of these isolates using hemolysis tests and Galleria mellonella larvae infection models. The results showed that ST463 isolates were more virulent than other isolates. In conclusion, pyocyanin-producing ST463 P. aeruginosa, carrying diverse virulence genes, is a potential high-risk clone.